Lessons from mouse models in the impact of risk factors on the genesis of childhood B-cell leukemia - Casado-García, Ana; Isidro-Hernández, Marta; Alemán-Arteaga, Silvia; Ruiz-Corzo, Belén; Riesco, Susana; Prieto-Matos, Pablo; Sánchez, Lucía; Sánchez-García, Isidro; Vicente-Dueñas, Carolina (Frontiers in Immunology, 2023)
B-cell acute lymphoblastic leukemia (B-ALL) stands as the primary contributor to childhood cancer-related mortality on a global scale. The development of the most conventional forms of this disease has been proposed to be conducted by two different steps influenced by different types of risk factors. The first step is led by a genetic insult that is presumably acquired before birth that transforms a healthy cell into a preleukemic one, which that is maintained untransformed until the second step takes place. This necessary next step to leukemia development will be triggered by different risk factors to which children are exposed after birth. Mouse Murine models that recapitulate the stepwise progression of B-ALL have been instrumental in identifying environmental and genetic factors that contribute to disease risk. Recent evidence from these models has demonstrated that specific environmental risk factors, such as common infections or gut microbiome dysbiosis, induce immune stress, driving the Con formato: Fuente: (Predeterminada) +Cuerpo (Calibri) transformation of preleukemic cells, and harboring genetic alterations, into fully transformed leukemic cells. Such models serve as valuable tools for investigating the mechanisms underlying preleukemic events and can aid in the development of preventive strategiesapproaches for childhood leukemia in child. Here, we discuss the existing knowledge, learned from mouse models, of the impact of genetic and environmental risk factors on childhood B-ALL evolution and how B-ALL prevention could be reached by interfering with preleukemic cells.